Frost/Dew Point Temperature and Relative Humidity Measurements: Primary and Secondary Calibration Methods - Furtado Andreia; Zenebe Fitsum; Subas Özkan; Schwinghammer Michael; Giri Praveen (EPJ Web of Conferences)
Humidity measurements are crucial across various industries to ensure product quality, safety, and process efficiency. These measurements can be expressed as absolute quantities, such as frost/dew point, temperatures point, tf/td, or as relative humidity, U, which relates to saturation at a given temperature. Chilled-mirror hygrometers are widely used in high-precision industrial and research applications due to their broad measurement range, stability, and accuracy. Ensuring metrological traceability requires rigorous calibration using traceable methods. The DAkkS-accredited Calibration Laboratory of Process Insights follows DKD-R 5-8 [1] guidelines and meets ISO 17025 [2] requirements, employing both primary and secondary calibration methods for tf/td over the range [-90, 95] °C, and U over the range [1, 98] %rh. Primary calibration achieves the lowest uncertainties using in-house 1-pressure and 2-pressure humidity (Utf/tf : 0.4 K - 45 mK and UU: 0.10 - 0.39 %rh), while secondary calibration relies on stable CM hygrometers and commercial humidity generators (Utf/tf : 0.54 K - 70 mK and UU: 0.10 - 0.49 %rh). For relative humidity calibration, both tf/td [1] and temperature [3] sensors require calibration. Humidity calculations follow established references, ensuring high accuracy [4, 7-8]. This work outlines the methodologies and challenges in maintaining traceability and accuracy in high accuracy humidity measurements at PI Cal.